Development of procedures for determining the parameters of an aircraft servo actuator - Kononykhin, Eugene (Eastern-European Journal of Enterprise Technologies, 2019)
Main trends in the use of electro-hydraulic actuators and requirements to parameters were discussed. Necessity of using automatic methods for testing an electro-hydraulic actuator together with the standard hardware of the electronic control unit was substantiated. The procedures for testing the control loop of an electro-hydraulic actuator set forth in this study make it possible to eliminate effects of mutual influence of dynamic and static characteristics of the actuator and hardware of the electronic control unit. Procedures for automatic identification of the actuator model and procedures for automatic determination of main parameters and characteristics of the actuator such as zero shift, dead space, amplitude-frequency, phase-frequency and speed characteristics have been proposed. When introducing the proposed procedures, the problem of processing high-speed characteristics of the actuator having high noisiness associated with the pulse nature of the derivative of the discrete signal of the actuator position (12 bits) was solved. In order to avoid introduction of errors in the waveform, in addition to standard digital filtering methods, it was proposed to approximate the noisy actuator characteristic by means of the Bezier curve. A procedure was proposed to record hysteresis of the speed characteristic by means of a cycle of continuous change of speed of movement of the output link of the actuator during the working stroke. The method for automatic identification of a simplified actuator model can significantly reduce labor costs in processing of experimental data. The parameters of the actuator model obtained for various deviations in parameters and various actuator operating conditions (external factors) can improve quality of synthesis of control algorithms